New Space Era : Characteristics of the New Space Industry Landscape - Baber, William W.; Ojala, Arto (Palgrave Macmillan, 2024)
In recent decades, the space industry has undergone enormous changes, transitioning from government-led space projects (referred to as “old space”) toward a more entrepreneurial and commercial utilization of space by private firms (termed “new space”). Due to these rapid changes, there is a pressing need for up-to-date insights into the field, encompassing its theories and characteristics, particularly concerning business activities related to space. In this chapter, we present five propositions for further study and more detailed investigation. These propositions are based on current literature and qualitative data gathered from 10 experts working in key roles within the space industry. Finally, the chapter identifies key theoretical elements that help elucidate how the space business is evolving and its likely trajectory in the near future.
Keywords: Space business; New Space; Resilience; Regulation; fi=Kansainvälinen liiketoiminta|en=International Business|